Digital Transformation of Government: An Applied Science Approach to Smart Governance in Urban SDG Frameworks - Syamsu Alam; Andi Syamsir; Rusdi Rusdi; Sugiarto Sugiarto; Basri Bado (International Journal of Engineering, Science and Information Technology, 2025)
This study applies an applied science approach to examine digital transformation in regional development, focusing on the Electronic-Based Government System (SPBE) and Smart Governance in Makassar City, Indonesia. The research evaluates the effectiveness, transparency, and contribution of technology-based governance systems toward achieving the Sustainable Development Goals (SDGs), particularly in strengthening urban governance performance. Employing a qualitative design that integrates Triangulation and the Logical Framework Analysis (LFA) method, this study investigates the practical impact of smart government initiatives and their correlation with development-oriented performance indicators. Findings reveal that insufficient interoperability of standards, protocols, and technologies impedes seamless data exchange across platforms, applications, and devices. This technical limitation has constrained Makassar’s smart governance outcomes, reflected in weak performance related to competitiveness, service efficiency, employment levels, and life expectancy. The study also identifies inadequate investment in smart infrastructure, research and development, and institutional capacity, which collectively hinder the realization of a data-driven, adaptive governance ecosystem. From an applied science perspective, this research underscores the necessity of strengthening interoperable digital architectures, ICT infrastructure, and human resource competencies to enhance system integration and decision support. By advancing engineering-based solutions for interoperability and data governance, regional governments can achieve higher levels of efficiency, transparency, and sustainability. The proposed framework provides a technological roadmap for aligning local smart city strategies with global development targets, demonstrating how applied digital innovations can bridge governance effectiveness and socio-development resilience in the context of sustainable regional transformation.